The Development of Gravity Comic Learning Media Based on Gorontalo Culture (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The aim of the study was to develop Gravity comic learning media based on Gorontalo culture for V grade Elementary School students. The type of the research was developmental referring to the design of 4-D model according to Thiagarajan, Semmel, and Semmel (1974) which consisted of 4 stages; define, design, develop and disseminate. The results of this study indicated that the developed gravity comic are valid and could increase students’ responses to learning. This cultural-based comic introduces Gorontalo regional cultures. The percentage of the students’ active participation was 93.27% for limited trial and the average students’ active participation in field trial was 94.94%. The students’ learning result gave 86.75% of classical completeness data for the limited test class, while the field test class obtained an average percentage of 87.37%, and categorized as very good. Therefore, the developed Comic of Gravity materials was declared valid, practical and effective. In sum, it would be useful for science learning process in grade V of Elementary School.